Application of Authentic Assessment to My Daily Assignment Themes in Class II - Mulyani, Hari (Program Magister Teknologi Pendidikan Universitas Jambi, 2020)
This research aims to determine and describe implementation authentic assessment on the theme of my daily assignments which have been carried out in class II elementary school 77/1 Penerokan. This research was conducted using a qualitative descriptive method, namely the subjects were one principal and one homeroom teacher of class II elementary school 77/ 1 Penerokan. To collect data, observations, interviews and documentation with data analysis techniques using three flows, namely, reduction data, display data and draw conclusions.The results showed that at elementary school 77/1 Penerokan there were applying authentic assessment in learning on the themes of my daily assignments. The teacher has carried out appropriate assessment steps, among others determine standards, determine assessment techniques, determine criteria, determine rubrics, carry out assessments and provide scores or grades. The teacher carries out authentic assessment techniques on the themes of my daily assignments between others on attitude assessment using observation techniques; on assessment knowledge of using written test techniques, oral tests, assignments; and on skills assessment using performance assessment, product assessment and portfolio assessment. Teachers experience obstacles in implementing assessments authenticity, including time constraints and student constraints.